Pest Resistance Management and Transgenic Plant Deployment: Perspectives and Policy Recommendations for the Developing World - Whalon, Mark E.; Norris, Deborah L. (International Service for National Agricultural Research, 2001)
Insect pests, weeds and diseases are a major cause of economic loss to farmers throughout the world. The widespread availability of synthetic insecticides, herbicides, and fungicides has allowed most countries to manage these pests. However, reliance on chemical controls has led to new problems and concerns, including: 1) pest resistance, 2) health impacts on farmers and farm workers, 3) pesticide residues in food, 4) destruction of beneficial organisms such as pollinators, 5) pollution of surface and ground water, and 6) reduction of biodiversity, and impact on non-target species, including some mammals, birds, and fish. "Resistance" is the biological process through which a pest population is selected to survive a pesticide. Pests are much more difficult and costly to control once they evolve resistance, and, in some instances, pests can no longer be controlled with pesticides. Since resistance has a genetic basis and the environmental and ecological factors that affect its development are known, it can be managed. "Resistance management" is the process of controlling resistance development in insect, disease, and weed pest populations.